ARTIFICIAL INTELLIGENCE AND BEHAVIOR CHANGE: IMPLEMENTING AI STARTUPS IN SPORTS AND HEALTH DOMAINS - Shahram Ahanjan; Mohsen Pasban; Hadi Miri; Behzad Jaybashi; Ghazal Ahanjan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Artificial intelligence (AI) is transforming the sports and health industries by providing advanced tools to facilitate behavior change. Integrating psychological aspects such as motivation, emotional regulation, and self-regulation with AI offers a promising avenue for personalized and effective behavior change interventions. However, challenges remain in terms of psychological resistance, ethical concerns, and technological limitations.Objective: This narrative review explores the role of AI in behavior change, focusing on psychological dimensions and the implementation of AI startups in sports and health domains.Methods and Materials: A comprehensive literature search was conducted across multiple databases, including PubMed, PsycINFO, IEEE Xplore, and Scopus. Studies published between 2010 and 2024 were included, focusing on AI applications in behavior change and their psychological impacts in sports and health. Data were extracted and thematically analyzed to identify key trends, challenges, and future directions.Findings: AI-driven interventions in sports are enhancing both physical performance and psychological well-being, with applications in mental training, stress management, and resilience building. Health startups are utilizing AI for mental health interventions, including apps targeting anxiety, depression, and behavior modification. However, psychological barriers such as fear of AI, lack of trust, and reduced human connection hinder adoption. Ethical dilemmas around data privacy and dependency on AI for emotional support pose additional challenges. Nonetheless, innovations in AI, including the integration of cognitive-behavioral models and real-time feedback systems, show promising potential for promoting holistic well-being.Conclusion: AI can effectively support behavior change through psychological mechanisms, but success depends on addressing ethical concerns, overcoming psychological resistance, and ensuring the complementary role of AI alongside human professionals. Future research should focus on improving AI's capacity for emotional intelligence, understanding long-term psychological effects, and fostering human-AI collaboration for health and sports interventions.